(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The research aims to demonstrate the importance of the role played by the compliance controller in controlling electronic payment tools in order to ensure the success of the bank with regard to its compliance with the laws, regulations and regulations of the Central Bank of Iraq and to reduce the risks of electronic payment. In control of electronic payment tools? The research relied on solving its problems on the hypothesis of influence, where the first main effect hypothesis was: There is no statistically significant effect of the compliance controller with its combined dimensions in the electronic payment tools, and the questionnaire form was also used to collect data and the community was the 25 private Iraqi commercial banks. A sample of them (10 banks) was selected, of which 73 questionnaires were distributed to them, 7 questionnaires were distributed to each bank, and the researcher relied on analyzing the data in descriptive statistics on the frequency distribution and percentage for the purpose of describing the data for the research sample test, and the arithmetic mean to measure the average Sample answers and knowing the level of the variables for the purposes of analysis and standard deviation to find out the homogeneity or dispersion of the answers of the sample and the coefficient of difference, In the inferential statistics, the reliability coefficient was used to test the validity of the questionnaire and the Pearson correlation coefficient to test the strength of the correlation between the research variables and linear regression to determine the effect of the variables. By dealing with daily reports within a specific time limit to find an appropriate solution for it in the same period and before the problem in banks worsens. As for the most prominent recommendations, focus more on the function of the compliance controller in commercial banks because of its positive role on high-risk electronic payment tools, and strictness in Implementing the policy of the Central Bank of Iraq in dealing with violating banks within a period of Time.